How Brand Disclosure Timing and Brand Prominence Influence Consumer's Intention to Share Branded Entertainment Content. Issue 1 (May 2018) - Choi, Dongwon; Bang, Hyejin; Wojdynski, Bartosz W.; Lee, Yen-I; Keib, Kate M.
The spread of branded entertainment video online relies on the consumer's referral decision, an initial decision to share the video. This study investigates how brand prominence and brand disclosure timing in a branded entertainment video interact with each other and affect viewers' persuasion knowledge, sharing intention, and visual attention. The study finds that when the branded nature of the video was disclosed prior to viewing the video content, prominent placement generated greater conceptual/attitudinal persuasion knowledge compared to subtle placement. Accordingly, greater persuasion knowledge resulted in less sharing intention and active avoidance in visual attention to the brand in the video content. On the other hand, when the brand was disclosed after the video content, there were no significant effects of brand prominence on conceptual or attitudinal persuasion knowledge, or on sharing intention. Further, the study shed light on the underlying mechanism of interaction effect by demonstrating the mediating role of attitudinal persuasion knowledge and enjoyment. Practical and theoretical implications are discussed.